Higher Education Students’ perceptions of Sustainable Development in Portugal - Aleixo, Ana (2021)
Higher education institutions play an increasingly important role in advancing sustainable development. Various studies have demonstrated the key contribution made by teachers to achieving sustainable development. However, few works have addressed students’ perceptions in this regard and given that the students of today will be the main influencers and decision-makers of the future, a greater understanding of their beliefs and attitudes towards sustainable development should be gleaned. The aim of this research is to analyse the perceptions of sustainable development held by students at Portuguese public higher education institutions. To this end, a descriptive and exploratory study was conducted by administering an online questionnaire. The sample is made up of 1257 students from different Portuguese public higher education institutions (68.6% women; average age 24.96 years). The results show that although the students recognise the importance of sustainable development and most of them have already heard about the sustainable development goals (16% never heard about them), they believe that the higher education institutions could and should give more training on this matter. Most students state that they would accept a lower salary from a company with a good social and environmental performance in some circumstances. The majority also have pro-sustainability habits and behaviours. Most of the students are concerned about climate change, most speak of some reusing, reducing and recycling practices, but fewer students contribute to sustainable development by participating in activities (e.g., environmental or community volunteering) organised by environmental organisations or the higher education institution. Differences in the behaviours and habits related to sustainability were observed between the students of different genders, ages and scientific areas. The results further present four clusters of students regarding their perception of sustainable development and related practices. The largest cluster (about 45%) includes students who are more concerned about climate change, actively contribute to sustainable development with reuse, reduction and recycling practices, and participate in organised activities to promote the protection of the environment or society. The smallest cluster (about 8%) includes students who are still sceptical about climate change and therefore adopt less environmentally friendly practices. Five years after the publication of the sustainable development goals, students feel that sustainability is starting to be integrated in education. However, the impact on their behaviours and attitudes remains moderate.